Production of Glucose 6-Phosphate From a Cellulosic Feedstock in a One Pot Multi-Enzyme Synthesis - Usvalampi, Anne; Li, He; Frey, Alexander D. (Frontiers in Bioengineering and Biotechnology, 2021)
Glucose 6-phosphate is the phosphorylated form of glucose and is used as a reagent in enzymatic assays. Current production occurs via a multi-step chemical synthesis. In this study we established a fully enzymatic route for the synthesis of glucose 6-phosphate from cellulose. As the enzymatic phosphorylation requires ATP as phosphoryl donor, the use of a cofactor regeneration system is required. We evaluated Escherichia coli glucokinase and Saccharomyces cerevisiae hexokinase (HK) for the phosphorylation reaction and Pseudomonas aeruginosa polyphosphate kinase 2 (PPK2) for ATP regeneration. All three enzymes were characterized in terms of temperature and pH optimum and the effects of substrates and products concentrations on enzymatic activities. After optimization of the conditions, we achieved a 85% conversion of glucose into glucose 6-phosphate using the HK/PPK2 activities within a 24-hours reaction resulting in 12.56 g/l of glucose 6-phosphate. Finally, we demonstrated the glucose 6-phosphate formation from microcrystalline cellulose in a one-pot reaction comprising Aspergillus niger cellulase for glucose release and HK/PPK2 activities. We achieved a 77% conversion of released glucose into glucose 6-phosphate, however at the expense of a lower glucose 6-phosphate yield of 1.17 g/l. Overall, our study shows an alternative approach for synthesis of glucose 6-phosphate that can be used to valorize biomass derived cellulose.